Prosumption: bibliometric analysis using HistCite and VOSviewer. Issue 3 (23rd August 2019) - Shah, Syed Hamad Hassan; Lei, Shen; Ali, Muhammad; Doronin, Dmitrii; Hussain, Syed Talib
Abstract : Purpose: Over the past decade, the term prosumption (denoting simultaneous consumption and production) has exhibited a dramatic increase in frequency of use in publications in the social sciences and business studies. This paper aims to explore the current state of research into prosumption, particularly related to marketing. Design/methodology/approach: This study systematically reviews papers on prosumption extracted from the Web of Science, using two bibliometric analyses on 20 years of data: citation counts from HistCite and bibliographic coupling and cartography analysis from the visualization of similarities software VOSviewer. A total of 75 papers on prosumption were found from the period 1997-2017, and the most influential authors, articles, journals, institutions and countries among these were determined. Furthermore, bibliographic coupling and most co-occurrent keywords in the title, keywords and abstracts were found. Findings: This study found that the USA and the UK were the most influential among prosumption publications. Ritzer was the most prominent author and Journal of Consumer Culture was the top-ranking journal. Three clusters were found using bibliographic coupling and cartography analysis: prosumer and co-creation, prosumer and user-generated content and prosumer and informational capital. Research limitations/implications: This analysis provided a basis for conceptualizing publications on prosumption related to business and sociology in the discipline of marketing. Content analysis found that prosumption research in marketing is in early stages: little quantitative study has been conducted yet. Researchers have not yet constructed a quantitative measure for prosumption. Practical implications: Business firms can engage prosumers to gain market share and competitive advantage, especially relative to value co-creation, with near-zero marginal cost. Originality/value: This may be the first bibliometric analysis and systematic review of prosumption research in marketing studies. The achievements of this paper open new avenues for other prosumption researchers.